Replacement of the Benzylpiperidine Moiety with Fluorinated Phenylalkyl Side Chains for the Development of GluN2B Receptor Ligands. (14th November 2018) - Thum, Simone; Schepmann, Dirk; Kalinin, Dmitrii V.; Ametamey, Simon M.; Wünsch, Bernhard
Abstract: The 4‐benzylpiperidine moiety is a central structural element of potent N ‐methyl‐d ‐aspartate (NMDA) receptor antagonists containing the GluN2B subunit. To obtain novel GluN2B ligands suitable for positron emission tomography, the benzylpiperidine moiety was replaced with fluorinated ω‐phenylalkylamino groups. For this purpose three primary propyl‐ and butylamines7 a –c and one butyraldehyde7 d bearing a fluorine atom and an ω‐phenyl moiety were prepared in 3‐ to 7‐step syntheses. Compounds7 a –d were attached to various scaffolds of potent GluN2B antagonists (scaffold hopping) instead of the original 4‐benzylpiperidine moiety. Although benzoxazol‐2‐ones and indoles with a benzylpiperidine moiety show high GluN2B affinity, the corresponding fluorophenylalkylamine derivatives did not result in high Glu2B affinity. Moderate GluN2B affinity was observed for a 3‐(fluoroalkyl)‐substituted tetrahydro‐1 H ‐3‐benzazepine ( K i =239 nm ). However, high GluN2B affinity was obtained for the tetrahydro‐5 H ‐benzo[7]annulen‐7‐amines12 a –c ( K i =17–30 nm ). Docking studies resulted in the same binding pose for12 a as for the lead compound Ro 25‐6981. It can be concluded that some GluN2B ligands (benzoxazolones, indoles) do not tolerate replacement of the 4‐benzylpiperidine moiety with flexible fluorinated phenylalkyl side chains, but other scaffolds such as tetrahydro‐3‐benzazepines and ‐benzo[7]annulenes retain interaction with NMDA receptors containing the GluN2B subunit. Abstract : GluN2B tracer ! To replace the 4‐benzylpiperidine scaffold of potent GluN2B antagonists with fluorinated structural elements, novel fluorinated ω‐phenylalkylamines and one butyraldehyde were synthesized. These building blocks were introduced into benzoxazol‐2‐one, indole, tetrahydro‐1 H ‐3‐benzazepine, and tetrahydro‐5 H ‐benzo[7]annulen‐7‐amine scaffolds. This scaffold hopping showed that the flexible fluorinated phenylalkylamine substructure eliminates GluN2B affinity when combined with benzoxazolone and indole scaffolds, but retains moderate to high GluN2B affinity upon introduction into 3‐benzazepine and benzo[7]annulene scaffolds.